The Influence of Oral Cryotherapy on Prevention from Mucositis in Cancer Patients under Chemotherapy in RSUP H. Adam Malik, Medan (Indian Journal of Public Health Research & Development, 2020)
Objects: to identify effectiveness of oral cryotherapy on prevention from mucositis in cancer patients underchemotherapy.Methods: the study used quasi experimental method with pre-post test with control group. The sampleswere 32 patients for intervention group and control group, taken by using consecutive sampling technique.Mucositis was measured by using questionnaires on Oral Assessment Guide (OAG) while the data analyzedby Wilcoxon test and Mann Whitney test.Results: The result showed, in the post intervention in the intervention group, 24 respondents were notaffected by mucositis at p-value=0.008 (p
Keywords: Oral cryotherapy; Mucocities; Cancer; Chemotherapy